Madres Invisibles: Cuatro casos de los años 1856-1858 que muestran las razones que tenían las madres para abandonar a sus hijos - Schuen, Freya (Avisos de Viena, 2023)
In just nine words lies the entirety of a tragically short life—a tale of a child and its family. Through archival records from Madrid's Inclusa, we glimpse into the sorrowful narrative of a mother and son, forever separated by circumstances. The note, retrieved from the digitized archives, unveils the grim fate of a child wrapped in cotton, already deceased upon arrival. Whether delivered lifeless or abandoned in dire condition, the infant's survival odds were bleak in an era where maternal abandonment was rife. Drawing parallels with ancient myths and biblical narratives, we confront the universal theme of maternal sacrifice amidst societal hardships. The records, spanning from 1856 to 1858, offer poignant insights into the agonizing decisions faced by mothers during this period. Under what circumstances did these women relinquish their offspring?